Status Hak Tanggungan Pada Pembiayaan Kepemilikan Rumah Di Akad Musyarakah Mutana Qisah (MMQ) - Laksono, Febrian Dwi; Luth, Thohir; Hamidah, Siti (Jurnal Hukum & Pembangunan, 2020)
The prevailing legal stipulations on the contract of the Musyarakah Mutanaqisah (MMQ) financing are occurred legal uncertainty, which is caused by obscurity of the encumbrance regulations for land relating to financing with the MMQ contract. One of arising legal issue in the MMQ financing mechanism is a blurring of the norms contained in Law Number 4 of 1996 concerning Encumbrance Right over Land And Land-Related Objects (UUHT). The obscurity is caused by unclear stipulating sharia financing or specifically financing with the MMQ contract in UUHT. One of the provisions that reflecting this lack of clarity is to examine the description of the definition of Encumbrance Right. The UUHT definition only explains that the Encumbrance Right is security right which is imposed on a land title to pay off a debt and making the position preferred for Encumbrance. The results showed that the concept of the debt and credit relationship in article 3 of the UUHT was not only limited to the legal relationship between the lending and borrowing as in the concept of the loan-lending agreement in article 1754 of the Civil Code (Civil Code) but also other agreements that have obligatory nature.